PENGARUH TATA KELOLA PERUSAHAAN, KUALITAS TANGGUNG JAWAB SOSIAL DAN KINERJA KEUANGAN TERHADAP PENGHINDARAN PAJAK - Hestika; Setiawan, Irwan (Publika Citra Media, 2024)
This study aims to determine the influence of corporate governance, social responsibility and financial performance on tax avoidance. The population in this study is Manufacturing Companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2019-2023 period. In this study, the data used is secondary data, the sample was selected using the method Purposive Sampling and produced as many as 31 samples. Data analysis in the study used multiple regression analysis using e-views software version 10. The results of the study show that independent commissioners do not have a significant effect on tax avoidance, the audit committee has a significant effect on tax avoidance, corporate social responsibility does not have a significant effect on tax avoidance, financial performance has a significant effect on tax avoidance, and governance, social responsibility and financial performance simultaneously affect tax avoidance.